Using longitudinal metallic stringers to reduce wave attenuation for water leakage detection in plastic pipes - Lima, L. P.M. [UNESP]; Bazani, M. A. [UNESP]; Paschoalini, A. T. [UNESP] (My University, 2020)
Many leakage detection techniques used in water distribution pipelines rely on the vibration response caused by the leak and, therefore, are limited by the capabilities of the pipe, fluid and its surroundings of carrying the leakage signal, and of the detection device used. In some cases, such as in cross-correlation of leak noise, the effective detection depends on low wave attenuation and the proper estimation of propagation velocity. Since attenuation depends on both the propagation mode and the medium, we propose a change in the pipes, usually made of plastic, to make them less attenuating: we add longitudinal metallic stringers to them. In this work, the pipe with stringers, now a longitudinally stiffened cylindrical shell, is treated in vacuo. The system's equations of motion and dispersion relationship are derived for one stringer attached to the shell. Analytical and numerical results from a finite element method simulation are compared and a significant decrease in attenuation is apparent. The numerical simulations also help understand what needs to be improved in the analytical model to better represent the proposed pipe.